Genome-Wide Identification and Characterization of Receptor-Like Protein Kinase 1 (RPK1) Gene Family in Triticum aestivum Under Drought Stress - Rahim, Amna Abdul; Uzair, Muhammad; Rehman, Nazia; Rehman, Obaid Ur; Zahra, Nageen; Khan, Muhammad Ramzan (Frontiers in Genetics, 2022)
Receptor-Like Protein Kinase (RPK) genes play crucial roles in plant growth and development processes, root architecture, and in abiotic stress regulation. A comprehensive study of RPK gene family has not been reported in bread wheat (Triticum aestivum). Here, we reported the genome-wide identification, characterization, and expression patterns of RPK gene family in wheat. Results confirmed 15 TaRPK genes, classified mainly into three sub-clades based on phylogenetic tree. The RPK genes were mapped on chromosome 1-3 in respective A, B, and D genomes. Gene structure, motif conservation, collinearity prediction and synteny analysis were carried out systematically. Gene ontology study revealed that TaRPK genes play vital role during molecular and biological processes. We also identified 18 putative miRNAs targeting TaRPK genes, suggesting their roles in growth, development, and stress responses. Cis-regulatory elements interpreted the presence of light related elements, hormone responsiveness, and abiotic stress related motifs in the promoter regions. The SWISS_MODEL predicted the successful models of TaRPK proteins with at least 30% identity to the template, widely accepted threshold for successful modeling. In-silico expression analysis in different tissues and stages suggested that TaRPK genes exhibited highest expression in root tissues. Moreover, qRT-PCR further validated the higher expression of TaRPK genes in roots of drought tolerant varieties, compared to the drought-susceptible variety. Collectively, the present study renders valuable information on the functioning of TaRPK genes in wheat that will be useful in further functional validation of these genes in future studies.